Peramalan Kinerja Keuangan PT Bank Syariah Bukopin Menggunakan Metode ARIMA Box-Jenkin - Irmatul Hasanah (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten,, 2022)
Public trust in banks can be influenced by the performance of a bank which can be seen from its profitability ratios. A decrease in the performance of a bank will lead to a decrease in the level of profitability of a bank. So that if there is a decrease in the level of profitability will cause a decrease in public trust in the bank. This study aims to predict the financial performance data of PT Bank Syariah Bukopin using the ARIMA Box-Jenkins method. The data used for this research is quarterly profitability ratio data for ROA and ROE for 2010-2020. This results shows that ARIMA(1,1,0) model can be used to find the value of ROA in th